Astyanax totae, a new characid species (Teleostei: Characidae) from the upper rio Iguaçu basin, southeastern Brazil - Carolina Ferreira Haluch; Vinícius Abilhoa (Neotropical Ichthyology)
A new species of characid fish, Astyanax totae, is described from a small tributary in the upper drainage of the rio Iguaçu, Paraná basin, Brazil. The new species is distinct from most species of Astyanax by the vertically elongated humeral spot, slightly expanded above the lateral line to posterodorsal margin of opercle, followed by a midlateral dark stripe expanded from the humeral region to the median caudal-fin rays, maxilla with 2 to 5 teeth (usually 3) and 15 to 18 branched anal-fin rays.